Controlled infection with a therapeutic virus defines the activation kinetics of human natural killer cells in vivo. (10th March 2015) - El-Sherbiny, Y M; Holmes, T D; Wetherill, L F; Black, E V I; Wilson, E B; Phillips, S L; Scott, G B; Adair, R A; Dave, R; Scott, K J; Morgan, R S M; Coffey, M; et al.
Summary: Human natural killer (NK) cells play an important role in anti-viral immunity. However, studying their activation kinetics during infection is highly problematic. A clinical trial of a therapeutic virus provided an opportunity to study human NK cell activation in vivo in a controlled manner. Ten colorectal cancer patients with liver metastases received between one and five doses of oncolytic reovirus prior to surgical resection of their tumour. NK cell surface expression of the interferon-inducible molecules CD69 and tetherin peaked 24–48 h post-infection, coincident with a peak of interferon-induced gene expression. The interferon response and NK cell activation were transient, declining by 96 h post-infection. Furthermore, neither NK cell activation nor the interferon response were sustained in patients undergoing multiple rounds of virus treatment. These results show that reovirus modulates human NK cell activity in vivo and suggest that this may contribute to any therapeutic effect of this oncolytic virus. Detection of a single, transient peak of activation, despite multiple treatment rounds, has implications for the design of reovirus-based therapy. Furthermore, our results suggest the existence of a post-infection refractory period when the interferon response and NK cell activation are blunted. This refractory period has been observed previously in animal models and may underlie the enhanced susceptibility to secondary infections that is seen following viral infection.